The Implementation of Fiqh Learning Based on Fathul Qarib in Pesantren - Zulfahri Husein; Darliana Sormin; Delila Sari Batubara (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Fiqh learning based on classical Islamic texts in pesantren plays an important role in shaping students’ religious understanding and worship practices. However, it often faces challenges such as limited instructional time and students’ varying levels of Arabic language proficiency. One of the classical texts used in Fiqh instruction is the Kitab Fathul Qarib, which requires systematic learning management. This study aims to describe the planning, implementation, and evaluation of Fiqh learning based on the Kitab Fathul Qarib at Al-Azhar Bi’Ibadillah Islamic Boarding School, South Tapanuli Regency. The research employed a qualitative approach using a case study design as proposed by Creswell. The informants consisted of Fiqh teachers, dormitory supervisors, and third-grade Tsanawiyah students selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that Fiqh learning is planned by aligning instructional materials and teaching methods with students’ abilities. The learning process is implemented through the bandongan and sorogan methods. Evaluation covers both academic aspects and practical worship practices, such as ablution and prayer, which are reinforced through mudzakarah activities and guidance from senior students. The study implies that Fiqh learning based on the Kitab Fathul Qarib is effective in improving students’ understanding and practice of Fiqh, although strengthening Arabic language skills and managing instructional time remain necessary.